(untitled) (Medico Legal Update, 2021)
Sepsis is a common illness; however, it strikes aged people and very young people in more tendency. The most susceptible age group of sepsis is children, and more specifically newborns and young infants. In addition, underlying health problems increase the risk of illness. The aim of this study is to determine prevalence of septicemia in children under five years in Al-Kut hospital for Gynecology obstetrics and pediatrics, numbers of cases are 135 patients. A descriptive analysis study design was used for the purpose is conducted at Al-Kut hospital for Gynecology obstetrics and pediatrics. There was significant differences in the prevalence of septicemia among children with different ages. The prevalence of septicemia was higher in the 1st month of age .Generally, prevalence of septicemia did not significantly affected by gender, however age is the most influencer since the infection was higher in children samples which were collected from stool isolates. At end, to reduce the complication and mortality of septicemia and to prevent sepsis formation infection including antibiotic-resistant pathogens related infection, research recommend a rapid diagnosis and effective treatment.